Skin Tone, Discrimination, and Allostatic Load in Middle-Aged and Older Puerto Ricans. Issue 7 (September 2021) - Cuevas, Adolfo G.; Abuelezam, Nadia N.; Chan, Sze Wan (Celine); Carvalho, Keri; Flores, Cecilia; Wang, Kaipeng; Mattei, Josiemer; Tucker, Katherine L.; Falcon, Luis M.
ABSTRACT: Objective: A growing body of research suggests that skin tone may be a health risk indicator for Hispanics. Black and darker-skinned Hispanics have worse mental and physical outcomes than White and lighter-skinned Hispanics. Discrimination exposure has been implicated as a risk factor that may explain the association between skin tone and health. However, there is scant research examining the interrelationship between skin tone, discrimination, and health, particularly among Puerto Ricans. We examine the interrelationships between two measures of skin tone, two measures of discrimination, and allostatic load (AL) among Puerto Rican adults. Methods: Using cross-sectional data from wave 3 of the Boston Puerto Rican Health Study ( n = 882), we examined the indirect association (IA) of skin tone on physiological dysregulated systems, also known as AL, through major discrimination and everyday discrimination. We tested these associations using two distinct measures of skin tone: interviewer-ascribed skin tone and spectrophotometer-measured skin tone. Results: Interviewer-ascribed skin tone was indirectly associated with AL through major discrimination (IA = 0.03, 95% confidence interval = 0.004 to 0.06). However, there was no evidence of an IA of interviewer-ascribed skin tone on AL through everyday discrimination (IA = −0.01, 95% confidence interval = −0.03 to 0.01). In addition, there was no evidence that spectrophotometer-measured skin tone was indirectly associated with AL through major discrimination or everyday discrimination. Conclusions: The sociocultural significance of skin tone may affect how Puerto Ricans are perceived and treated by others, which can, in turn, have physiological health consequences. Future research is needed to replicate these findings and examine the interrelationship between skin tone, discrimination, and other health outcomes. Abstract : Supplemental digital content is available in the text.